INTEGRATING TARGET CULTURE IN EFL CLASS - Tarwiyah, Siti (VISION, 2014)
AbstractLanguage is a part of culture. Language and culture are formulatedin the forms of concepts, propositions, memory, and inferencesor it can be seen through behavior patterns, arts, beliefs, institutionsand all other products of human work and thought. Eachspeech community has different ways of communicating information,ideas, attitudes, and standpoints. They have different normsof speech. Breaking the norms of speech results in communicationconstrains, misunderstanding between interlocutors. Teachers ofEFL class should have big concern in integrating target languageculture of the language being taught into their learning. This waystimulates studentsâ awareness of the target language culture whichlater results in effi cient global communication using the target language.Key Words: language, culture, cross-cultural communication, integrate,EFL class